Assessment of Obesity in medical students - et. al., Mrs. A. V. Rao, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Objective: Obesity is one of the root cause of various noncommunicable diseases like hypertension, coronary heart disease and type 2 DM. Obesity in childhood and adolescent is highly associated with increased risk of cardiovascular and metabolic diseases later in adult life. In general population obesity is measured with simple and effective tool, Body mass index (BMI). This study was planned to find out the obesity status of medical students those are health professionals serving the society. Methods: Study was carried out in I MBBS student after admission in the college at the time of medical check-up, anthropometric measurements such as weight and height were measured with maximum accuracy. BMI was calculated by Quetelet's Index & students were classified into normal (BMI = 18 to 24.99), overweight (BMI =24.99 to 29.99) & obese (BMI 30) groups. Results: 820 students (334 males and 486 females) were participated in this study. Normal BMI was found in 58.04 % students. 21.95% were found overweight and 10.00% were found obese. 10.00% students were found to be Underweight. Conclusions: Our data shows that the prevalence of obesity is high amongst medical students who are upcoming doctors..